THE ILLOCUTIONARY ACT OF HAZEL GRACE IN THE FAULT IN OUR STARS MOVIE - Juli Rachmadani Hasibuan, Septia Elisabeth Nainggolan and (LINGUISTICA, 2015)
This study deals with Illocutionary Act of Hazel Grace as the main character in The Fault in Our Stars movie. The objectives of the study was discovered the types of Illocutionary Act which were used by Hazel Grace as the main character and described in what contexts that she used in The Fault in Our Stars movie. The subject of this study was The Fault in Our Stars movie and each spoken words or the conversation by Hazel Grace that were written in The Fault in Our Stars movie script became the source of the data. The data were collected by browsing and downloading from internet. This study was conducted by using qualitative descriptive design. The result of analyzing types and the contexts of Illocutionary Act were used by Hazel Grace as main character such as representatives with 34.6% (236 utterances), directives with 24.3% (166 utterances), expressives with 22.2% (152 utterances), declaratives with 15.5% (106 utterances) and commissives with 3.4% (23 utterances) and made representative became the most dominant type. And representative context was the dominant context because The Fault in Our Stars movie used first person, main character™s point of view from perspective of the main character that Hazel Grace used like informing, describing, sharing, believing, stating a fact, assuming, predicting and also complaining which make her like a narrator in that movie because she informs, describes, shares about her diseases, her interests, her thought also about life or everything, and what she believe by herself.